2007
DOI: 10.1159/000099302
|View full text |Cite
|
Sign up to set email alerts
|

Intraocular Extension of Conjunctival Squamous Cell Carcinoma

Abstract: Conjunctival squamous carcinoma, which is regarded as a low-grade malignancy, usually originates at the limbus. Most cases remain superficial to the sclera. Intraocular invasion is rarely reported. We describe a woman misdiagnosed as conjunctivitis and pterygium before a clinical diagnosis of conjunctival squamous cell carcinoma. The diagnosis was made by histopathological examination of the biopsy specimen. Examination revealed an elevated mass on the nasal limbus extending intraocularly. White flaky mass occ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 17 publications
1
9
0
1
Order By: Relevance
“…In accordance with previous studies, there was a marked male preponderance in our series [3,12]. Mean age of patients in the current study was younger than reported in most other series [1,4,[13][14][15].…”
Section: Discussionsupporting
confidence: 90%
“…In accordance with previous studies, there was a marked male preponderance in our series [3,12]. Mean age of patients in the current study was younger than reported in most other series [1,4,[13][14][15].…”
Section: Discussionsupporting
confidence: 90%
“…Olasode et al, 9 in their case presentation that reported invasive SCC initially diagnosed as an inflamed pterygium, stressed that a high index of suspicion is crucial to prevent a delay in the diagnosis of an invasive condition and not to cause complete involvement of the eye. Similarly, Zhang et al 10 described a woman misdiagnosed with conjunctivitis and pterygium before a clinical diagnosis of conjunctival SCC was made.…”
Section: Discussionmentioning
confidence: 97%
“…For the other 2 cases, however, we suspect that a violation of the Bowman layer during the initial excision allowed for intracorneal stromal invasion. Intraocular involvement of conjunctival SCC occurring through emissary vessels near the area of the limbus has also been reported [15]. …”
Section: Discussionmentioning
confidence: 99%
“…Although the reported incidence rate ranges from 0.1 to 1.9 per 100,000 persons [4,5,6], OSSN remains the most common ocular surface tumor and conjunctival SCC is the most common ocular malignancy [7,8]. Conjunctival SCC has the potential to locally invade as well as metastasize, with a few case series [9,10,11,12] and case reports [13,14,15,16] identifying intracorneal, intraocular and orbital invasion [17] by conjunctival SCC.…”
Section: Introductionmentioning
confidence: 99%